Insect-based lipid for biodiesel production - Chung, Yiin Wong; Jun, Wei Lim; Yoshimitsu, Uemura; Fai, Kait Chong; Yin, Fong Yeong; Mohamad, Mardawani; Heri, Hermansyah (2018)
Insect biomass could be a potential feedstock for biodiesel production in Malaysia. In this study, the viability of black soldier fly (Hermetia illucens) and weevil (Rhynchophorus sp.) larvae for biodiesel production were evaluated. Black soldier fly (BSF) and weevil larvae were found to contain about 32% and 44% of lipid content in dry weight basis by using petroleum ether solvent extraction. After esterification and trans-esterification, BSF and weevil larvae derived biodiesel were detected to contain 84% and 88% of FAME correspondingly. The GC analysis showed that BSF derived biodiesel contained approximately 55% of C12:0, 12% of C14:0, 6% of C16:0 and 4% of C18:1 with low percentage of C10:0, C16:1, and C18:2. Meanwhile, weevil derived biodiesel showed around 40% of C16:0 and C18:1, 3% of C16:1 and C18:0, and low content of C14:0, C18:2, and C18:3. The FAME produced from BSF and weevil larvae were equivalent to the FAME derived from coconut and palm oil. Thus, replacement of edible plant seed oil by insect biomass in biodiesel production is achievable to avoid the concerns on food against fuel in Malaysia.